2023
DOI: 10.21203/rs.3.rs-2778213/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genotoxic effect of heavy metals on Nile tilapia (Oreochromis niloticus) species in an urban river in northeastern Brazil

Abstract: Chemical pollutants represent a leading problem for aquatic ecosystems, as they can induce genetic, biochemical, and physiological changes in the species of these ecosystems, thus compromising their adaptability and survival. The Capibaribe River runs through the state of Pernambuco, located in northeastern Brazil, and passes through areas of agricultural cultivation, densely populated cities, and industrial centers, primarily textiles. Despite its importance, few ecotoxicological studies have been conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Taslima, K et.al, reported that fish development stages such as blastula, gastrula, segmentation and hatching respond differently to the intoxication depending on the type of metals, mode of action, exposure period and concentration of heavy metals [19]. For instance, the study by silva, J.P et.al, on Nile tilapia (Oreochromis niloticus) has reported high values for markers of genetic damage with the highest concentration of metals, particularly Iron, Zinc, Manganese, Cadmium and Chromium [20]. Another study by Çiftçi, N et.al, [21] on the effects of copper (Cu) and zinc (Zn) on hepatosomatic index (HIS), Gonadosomatic index (GSI) and condition factor (CF) discovered that Cu and Zn caused HIS and CF to decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Taslima, K et.al, reported that fish development stages such as blastula, gastrula, segmentation and hatching respond differently to the intoxication depending on the type of metals, mode of action, exposure period and concentration of heavy metals [19]. For instance, the study by silva, J.P et.al, on Nile tilapia (Oreochromis niloticus) has reported high values for markers of genetic damage with the highest concentration of metals, particularly Iron, Zinc, Manganese, Cadmium and Chromium [20]. Another study by Çiftçi, N et.al, [21] on the effects of copper (Cu) and zinc (Zn) on hepatosomatic index (HIS), Gonadosomatic index (GSI) and condition factor (CF) discovered that Cu and Zn caused HIS and CF to decrease.…”
Section: Introductionmentioning
confidence: 99%